Characterization of 1-3 piezoelectric polymer composites -- a numerical and analytical evaluation procedure for thickness mode vibrations - Madhusudhana Rao, C.V.; Prasad, G. (Condensed Matter Physics, 2010)
Biomedical transducers widely employ piezoceramic polymer composites with 1-3 connectivity. The research is aimed at determining the effective material properties of these composites in the micrometer scale by simulation. Volume fraction of piezoceramic in the composite plays an important role in composite material properties as studied by several researchers. It is also noted that the fiber aspect ratio (a/l) also affects the composite material properties. Therefore it is intended to determine the effective material properties both analytically and by simulation using computer simulation software program ANSYS which implements finite element method (FEM). In the present work piezoelectric fiber composites are modeled, analyzed and then the results are verified by using analytical equations. Important conclusions are drawn to select the piezocomposite materials for transducer applications.